Model Pembelajaran Prosedural dalam Meningkatkan Keterampilan Membuat Aquascape bagi Siswa Tunarungu Ringan di SLB Negeri 2 Padang - Hidayatullah, Riski; Damri, Damri (Universitas Negeri Padang, 2024)
The research was carried out in class X SLB Negeri 2 Padang with five students with mild hearing impairment. Where it is held on Wednesday and Thursday. The day for this research was determined by the class teacher during lunch break. Data collection was carried out in creating Aquascape skills using research instruments in the form of action test techniques. This data collection was carried out at each stage of the research, first the pretest stage, namely the students' initial abilities, then the treatment stage with the procedural learning model, then continued with the posttest stage to test the children's abilities after being given the treatment stage, providing conclusions if the procedural learning model is effective in improving students' skills. class X mildly deaf in making aquascape. Data collection was carried out from the pre-test to the post-test stage, then tested using the Wilcoxon sign rank test, with the results of Z count = -2.032b, Probability or Asymp Sig (2-tailed) = 0.042. It can be seen that the calculated probability of Z is smaller than the specified probability (0.042 < 0.05), so that Ho is rejected and Ha is accepted.